Important Role of Parents in Stimulating the Emotional Ability of Early Children - Efriza Rahmadani; Tjipto Sumadi; Nurjanah Nurjanah (International Conferences on Early Childhood Education Proceedings, 2023)
Parents have a very important role in being a good role model or role model for children, especially in setting an example in behaving and acting, especially in the ability to manage emotions, early childhood does not yet have the mature ability to manage their own emotions so children need stimulation from parents in developing aspects of children's emotional abilities, but the facts on the ground show that some parents lack education on how to properly stimulate children's emotional abilities, so that children also lack the ability to regulate their emotions such as expressing emotions verbally and nonverbally and expressing emotions appropriately according to with the child's condition. This study aims to describe and explain the important role of parents in stimulating children's emotional development. This study uses a qualitative method with a literature study approach. Based on the results of the analysis of several relevant research journals, it is explained that children's emotional development is greatly influenced by the stimulation provided by the child's closest environment, especially the child's parents. The implication of this research is to educate parents about how to stimulate children's emotional development.